The effects of new firm formation on regional development over time: the case of Great Britain - Mueller, Pamela; van Stel, André; Storey, David J. (Springer, 2008)
This paper re-examines the link between new firm formation and subsequent employment growth. It investigates whether it is possible to have the wrong type of entrepreneurship – defined as new firm formation which leads to zero or even negative subsequent employment growth. It uses a very similar approach to that of Fritsch and Mueller (2004), confirming their findings that the employment impact of new firm formation is in three discrete phases. Then, using data for Great Britain, the paper shows the employment impact of new firm formation is significantly positive in the high enterprise counties of Great Britain. However, for the low enterprise counties, it shows that new firm formation has a negative effect on employment. Of the 15 low enterprise regions, 8 are Scottish (out of 9 Scottish regions in our data base) and three are North East Counties (out of four). Our findings imply that having the “wrong type of entrepreneurship” is indeed possible.
Keywords: New firm formation; Employment growth; Great Britain; Low entrepreneurial regions